IMPROVING STUDENTS’ ABILITY IN SPEAKING TROUGH ANIMATION MOVIE - Rosmita Ambarita; Vera Kristiana; Ratna Sari Dewi (Fakultas Sastra UMN AL Washliyah, 2022)
The objectives of the study were to investigate whether any significant difference in the improvement of students’ ability in story retelling using animation movie and without using animation movie. The total number of populations were 150 students. The sample in this study was 20 students. The researcher carried out an experimental study using statistical method called t-test. The researcher used two groups: experiment group and control group. In the control group the researcher used written text story, while in the experiment group, the researcher used animation movie. The data showed that the mean score of pre-test in experimental class was 73.5, while the mean score of pre-test in control group class was 74. Meanwhile, the mean score of post-test in experimental class was 78.1, and the mean score of post-test in control group class was 74.8. The statistical analysis showed that the minimum gained score of experimental class was 3 and the minimum gained score of control group class was 0. While, the highest gained score of experimental class was 8 and control group class was 2. The average gained score of experimental class was 4.6, and for control group class were 0.8. It can be concluded that the students’ speaking skill in experimental class that were given by the treatment through animation movie were improved more effectively than the control group.